Statin use is associated with lower risk of atrial fibrillation in women with coronary disease: the HERS trial. Issue 9 (28th January 2009) - Pellegrini, C N; Vittinghoff, E; Lin, F; Hulley, S B; Marcus, G M
Abstract : Objective: To determine the efficacy of statin treatment in atrial fibrillation (AF) prevention in women. Design: Cohort study using data obtained in the Heart and Estrogen/Progestin Replacement Study (HERS). Setting: Secondary analysis of a multicentre, randomised controlled clinical trial. Patients: 2673 Postmenopausal women with coronary disease. Main outcome measures: AF prevalence at baseline and incident AF over a mean follow-up of 4.1 years. Results: 88 Women with AF were identified: 29 at baseline and 59 during follow-up. Women with AF were significantly less likely to be taking a statin at study enrolment than those without AF (22% vs 37%, p = 0.003). Baseline statin use was associated with a 65% lower odds of having AF at baseline after controlling for age, race, history of myocardial infarction or revascularisation and history of heart failure (odds ratio 0.35, 95% confidence interval (CI) 0.13 to 0.93, p = 0.04). The risk of developing AF during the study among those free from AF at baseline, adjusted for the same covariates, was 55% less for those receiving statin treatment (hazard ratio 0.45, 95% CI 0.26 to 0.78, p = 0.004). Conclusions: Statin treatment is associated with a lower prevalence and incidence of AF after adjustment for potential confounders in postmenopausal women with coronary disease.